HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU TERHADAP KEJADIAN STUNTING PADA BALITA DI PUSKESMAS SUNGAI DURIAN KABUPATEN SINTANG TAHUN 2021 - Paskalia Tri Kurniati (STIKES ADVAITA MEDIKA TABANAN, 2022)
Stunting is a toddler with nutritional status based on length or height according to age when compared to the WHO standard, the Z-score value is less than -2SD and is categorized as very short if the Z-score value is less than -3SD (Ministry of Health, 2020). The purpose of the study was to determine the relationship between the level of knowledge and mother's attitude to the incidence of stunting in toddlers. Quantitative research method with cross sectional approach. The sampling technique used is Simple Random Sampling with 124 respondents who have toddlers. The research instrument used a closed questionnaire. The results of the Chi Square test analysis showed that there was a relationship between the mother's level of knowledge on the incidence of stunting in toddlers with a value (P = 0.000 <0.05) and an OR = 5.091, which means that mothers with less knowledge are at risk of having babies with stunting. The results of the Chi Square test analysis showed that there was a relationship between the mother's attitude towards the incidence of stunting in toddlers with a value (P = 0.001 <0.05) and an OR value = 3.712, which means that mothers with unsupportive attitudes are at risk of having babies with stunting events. It is recommended that health workers, especially nutrition workers and midwives, should be able to increase mother's knowledge and positive attitudes about proper nutrition for toddlers so that stunting can be prevented from an early age.